Diagnostic value of circulating lncRNA ANRIL and its correlation with coronary artery disease parameters - Hu,Yao (2019)
This study aimed to detect the expression of the long non-coding RNA (lncRNA) antisense non-coding RNA in the INK4 locus (ANRIL) and evaluate its correlation with disease risk, stenosis degree, inflammation, as well as overall survival (OS) in coronary artery disease (CAD) patients. A total of 230 patients who underwent diagnostic coronary angiography were consecutively recruited and assigned to CAD group (n=125) or control group (n=105) according to presence or absence of CAD. Gensini score was calculated to assess the severity of coronary artery damage. Plasma samples were collected and the expression ANRIL was detected in all participants. High-sensitivity C-reactive protein (hs-CRP), erythrocyte sedimentation rate (ESR), and cytokines including tumor necrosis factor-α (TNF-α), interleukin (IL)-1β, IL-6, IL-8, IL-10, and IL-17 in CAD patients were measured and OS was calculated. The relative expression of ANRIL was higher in CAD patients compared to controls (P<0.001). Receiver operating characteristic disclosed that ANRIL could distinguish CAD patients from controls with an area under the curve of 0.789 (95%CI: 0.731–0.847). Spearman's rank correlation test revealed that expression of ANRIL was positively correlated with Gensini score (P=0.001), levels of hs-CRP (P=0.001), ESR (P=0.038), TNF-α (P=0.004), and IL-6 (P<0.001), while negatively correlated with IL-10 level (P=0.008) in CAD patients. Kaplan-Meier curve revealed that high expression of ANRIL was associated with shorter OS (P=0.013). In conclusion, circulating ANRIL presented a good diagnostic value for CAD, and its high expression was associated with increased stenosis degree, raised inflammation, and poor OS in CAD patients.